Descriptions of a new subgenus and two new species of Atrichobrunettia Satchell (Diptera, Psychodidae) from the Neotropical region - Bravo, Freddy (Zootaxa, 2007)
Pachybrunettia subg. nov. is proposed for three Neotropical species of Atrichobrunettia: A. minuta Bravo from Bahia State, Brazil, A. trilobata sp.nov. from Amazonas State, Brazil and A. triangularis sp. nov from Pará State, Brazil. A key for identification of the Neotropical species of Atrichobrunettia is provided.